Epiphany travel and assisted-subjective personal introspection - Muller, C.; Woodside, Arch (Emerald Group Publishing Limited, 2012)
The study uses assisted-subjective personal introspection (ASPI) to analyze, assess, and critique a traveler's adventure as well as uncover the rationale behind why participating in a long trip with global implications was important to this traveler. Coupled with a thorough ASPI analysis, the study constructs an autoethnography: a form of autobiographical personal narrative that explores a traveler's experience of life. To equip the traveler with the necessary skills and tools to perform this analysis, the study includes research using ASPI and autoethnography. Finally, participating in Harvard University's "Implicit Association Test" (IAT) provides an external analysis and better understanding of own conscious- unconscious divergences. Using causal mapping, the study delineates a 14-week trip into weekly increments identifying positive and negative relationships while assessing the strengths of those relationships. The goal of this exercise is twofold: (1) to increase understanding of the human condition and (2) how that understanding can influence international marketing.